AGROFORESTRY PATTERNS USED BY THE COMMUNITY (Case Study In Sumber Makmur Village, Bandar Agung District, South Oku Regency, South Sumatra Province) - Rosianty, Yuli; Syahroni, S.P, M.Si, Sasua Hustati; Lestari, Bayu (Universitas Muhammadiyah Palembang, 2024)
This study aims to study the identification of agroforestry patterns in Sumber Makmur Village, Bandar Agung District, South OKU Regency, South Sumatra Province. The method used is interviews and observations to obtain primary data needed in the study, data analysis used in this study is qualitative descriptive analysis by narrating all the facts obtained in the analysis and then displayed in tabular form. From the results of the study, it is known that residents of Sumber Makmur Village, Bandar Agung District, South OKU Regency, South Sumatra Province. Have used an agroforestry system and chosen coffee and pepper plants as the main crops and lantoro as their shade, pepper is propagated on lantoro plants. All residents of Sumber Makmur Village work as farmers and have low education, but they are able to send their children to high schools, some even make their children state officials such as the TNI and Polri, are the results of coffee and pepper plantations/farms.